THE EFFECT OF FORENSIC ACCOUNTING, PROFESSIONAL SCEPTICISM AND FRAUD AUDIT TRAINING IN DETECTING FRAUD: A LITERATURE REVIEW - Atika, Bunga Filsa; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Forensic accounting, professional scepticism, and fraud audit training are various factors that may be influential in detecting fraud committed by clients. This article aims to analyze and identify the influence of forensic accounting, professional scepticism, and fraud audit training in detecting fraud. The research method used in this article is a literature review by analyzing and identifying various studies that have been conducted before. This research results in forensic accounting; professional scepticism is influential in detecting fraud. This shows that the better forensic accounting and professional scepticism, the better the examination will detect fraud. Fraud audit training does not significantly detect fraud because the cost is very expensive, so auditors cannot get full training.